2017
DOI: 10.1186/s12957-017-1216-2
|View full text |Cite
|
Sign up to set email alerts
|

Treating cancerous large airway stenosis with staging radioactive particle implantation guided by computed tomography and fiber bronchoscopy: a clinical study

Abstract: BackgroundThe purpose of this study is to investigate the clinical effectiveness of staging radioactive particle implantation guided by computed tomography (CT) and fiber–optic bronchoscopy in treating cancerous large airway stenosis.MethodsA total of 102 patients were included; 57 had undergone staging radioactive particle implantation guided by CT and fiber bronchoscopy and 45 did not. Patients were evaluated by CT and fiber–optic bronchoscopy to determine the feasibility of the implantation of radioactive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Radioactive seeds are implanted directly into the lesion as a kind of brachytherapy, and these seeds kill the tumour cells by consistently releasing rays [10]. 125 I radioactive seeds represent the most common type of permanently implanted seed, which can continuously release low-power γ-rays, with a half-life of 59.6 days and an available irradiation range of 17 mm, thus continuously inhibiting cell proliferation and angiogenesis as well as inducing apoptosis and killing tumour cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…Radioactive seeds are implanted directly into the lesion as a kind of brachytherapy, and these seeds kill the tumour cells by consistently releasing rays [10]. 125 I radioactive seeds represent the most common type of permanently implanted seed, which can continuously release low-power γ-rays, with a half-life of 59.6 days and an available irradiation range of 17 mm, thus continuously inhibiting cell proliferation and angiogenesis as well as inducing apoptosis and killing tumour cells [11].…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to mention that these survival rates are speculated to be higher in early-stage NSCLC, in which there is no metastatic disease. Several clinical studies investigated the effect of brachytherapy as an adjuvant therapy combined with other modalities such as chemotherapy, radiofrequency ablation and epidermal growth factor receptor tyrosine kinase inhibitors [ 28 , 29 , 30 , 31 , 32 ]. The addition of brachytherapy to the other modalities showed an increased effect, OS, PFS and QOL.…”
Section: Endobronchial Administrationmentioning
confidence: 99%
“…[ 32 ] RCT NSCLC III BT ChT 26 26 ChT n/a Mao, Y. [ 30 ] RCT NSCLC Advanced BT ChT 57 45 ChT n/a Wang, X. [ 31 ] RCT NSCLC IIIB, IV BT EGFR-TKI 54 54 EGFR-TKI n/a Chen, E. [ 26 ] Meta-analysis NSCLC Early-stage BT 308 n/a Chen, S. [ 28 ] RCT NSCLC I, IIA, III BT RFA 15 15 RFA n/a Chen, Z.K.…”
Section: Table A1mentioning
confidence: 99%
“…For the treatment of airway stenosis, a retrospective study analyzed the clinical effect of staging I (125) radioactive seed implantation under the guidance of computed tomography (CT) and fiberoptic bronchoscopy in the treatment of cancerous large airway stenosis. The results suggested that staging implantation of I-125 seeds can significantly improve the dyspnea index and improve survival and quality of life [14]; however, staging implantation will cause multiple implantation injuries. This study will assess the efficacy and feasibility of one-time CT-guided I (125) radioactive seed implantation in NSCLC patients with airway stenosis.…”
Section: Introductionmentioning
confidence: 99%